AJARAN MORAL KERIS JAWA - Nurhadi Siswanto (Corak : Jurnal Seni Kriya, 2013)
Java is so exotic. Java is beautiful. Being a Javanese as well as being any ethnicity, isnot a curse but a gift from God. Cultural values and wisdom not just tales of the parents alone,but it is a fact. One thing that is quite interesting to examine the Javanese is the existence of anheirloom called "keris". Keris has a long background history for the Javanese community. Keris,in the past was made with full of philosophy, made with a hope, desire, or even an ideal of thebuyerso that the keris as a final product reflects and represents all things non-objects of thebuyer. in Javanese keris contains many values and moral teachings. The values implicit inJavanese keris, include : (1) the doctrine of religiousity and awareness of the limitations ofhuman power (2) subjects to be always humble an not arrogant (3) theaching to always live inharmoni with nature (4) the doctrine for living in harmony with fellow human, and (5) thedoctrine of dynamism in life. Keywords: Teachings , Keris , Java  Jawa itu sangat eksotis. Jawa itu indah. Menjadi Jawa serta menjadi etnis manapun, bukanlahkutukan tapi hadiah dari Tuhan. Nilai-nilai budaya dan kearifan bukan hanya cerita orang tuasaja, tapi itu adalah fakta. Satu hal yang cukup menarik untuk memeriksa orang Jawa adalahadanya pusaka yang disebut "keris". Keris memiliki latar belakang sejarah yang panjang bagimasyarakat Jawa. Keris, di masa lalu itu dibuat dengan penuh filsafat, dibuat dengan harapan,keinginan, atau bahkan ideal-pembeli sehingga keris sebagai produk akhir mencerminkan danmewakili semua hal-hal non- benda pembeli. dalam keris Jawa mengandung banyak nilai-nilaidan ajaran moral. Nilai-nilai yang tersirat dalam keris Jawa, meliputi: (1) doktrin religiusitas dankesadaran akan keterbatasan daya manusia (2) pelajaran untuk selalu rendah hati yang tidaksombong (3) theaching untuk selalu hidup dalam harmoni dengan alam (4) doktrin untuk hidupharmonis dengan sesama manusia, dan (5) ajaran tentang dinamika dalam kehidupan. Kata kunci: Ajaran, Keris, Jawa